2020
DOI: 10.33545/pathol.2020.v3.i2c.249
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of prostatic lesions at tertiary care centre

Abstract: IntroductionDiseases of prostate gland are important source of morbidity and mortality in male patients. The number of cases has continuously increased over the past decades, partly due to the higher life expectancy. The spectrum of diseases consists of inflammatory conditions, hyperplasia and malignancy. Prostate biopsy is essential to detect cancer and other benign conditions. There are other modalities of diagnosis, comprising of radiology and prostatic biomarkers. However, biopsy with histopathological exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 11 publications
5
9
0
Order By: Relevance
“…The results of this study infer that benign prostatic hyperplasia was the most commonly diagnosed lesion of the prostate gland (88.9%), was isolated in most of the cases, and was most frequently seen in 61-70 years of age. Similar results have been found in a study conducted in India, a neighbouring country of Pakistan 21 . A study conducted at Dow University of Health Sciences Karachi in 2013 reported the frequency of benign prostatic hyperplasia to be 87.5% 22 .…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study infer that benign prostatic hyperplasia was the most commonly diagnosed lesion of the prostate gland (88.9%), was isolated in most of the cases, and was most frequently seen in 61-70 years of age. Similar results have been found in a study conducted in India, a neighbouring country of Pakistan 21 . A study conducted at Dow University of Health Sciences Karachi in 2013 reported the frequency of benign prostatic hyperplasia to be 87.5% 22 .…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with Aslam et al, their study reported that majority malignant cases were prevalent in the age group of 60-70 years. 19 Similar findings have been reported in other national studies 20,21 The Gleason score is an important parameter for clinical outcome in prostate cancer patients and is an important prognostic tool for the pathologists. 22 Most of the cases in our study were reported to have Gleason score of 7 (…”
Section: (Table-i)supporting
confidence: 80%
“…Prostate is a glandular organ that is located at the base of urinary bladder in males (1). Its main function is to produce the secretions that provide nutrition to the sperm cells and also help the sperm cells to survive the hostile environment in female genital tract (1). It has a central, peripheral, periurethral and transitional zone on gross examination (1).…”
Section: Introductionmentioning
confidence: 99%
“…Its main function is to produce the secretions that provide nutrition to the sperm cells and also help the sperm cells to survive the hostile environment in female genital tract (1). It has a central, peripheral, periurethral and transitional zone on gross examination (1). Under light microscope, the gland has abundant glands having a double layer epithelium i.e basal cuboidal cells and inner columnar cells (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation